Carbon from agricultural waste as an adsorbent in the removal of chromium and nickel ions from aqueous solution - Nor Harlina, Haji Hassan
The objectives of this study were to produce carbon from sugarcane bagasse and rice straw by pyrolysis technique as an adsorbent for heavy metal removal and to determine the optimum condition with respect to contact time, pH of solution, adsorbent doses, particle sizes of adsorbent, initial metal concentration and temperature. Also adsorption isotherm and adsorption kinetic behavior ofnickel(II) and chromium(VI) removal by each adsorbent will be determined. Sugarcane bagasse and rice straw are inexpensive and locally available agricultural waste. The raw materials were pyrolized at different temperatures ranging from 300 - 700 °c for 30 minutes with the average heating rate of 30°C/minute. The adsorbents were characterized for the yield, density, pH, ash content, moisture content, surface area and porosity by using BET surface area and porosity analyzer, functional groups by using Fourier Transform Infrared, surface morphology by using Scanning Electron Microscope and element and chemical composition by using Energy Dispersive X-ray. Adsorptions were found to be effected by pyrolyzing temperature and surface area. The adsorbents that produced at 700°C have been chosen for this adsorption study because it produced the highest percentage of removal. The maximum removal efficiency of Ni(II) on RSC and SBC as 85.65% and 21. 79 %, respectively and Cr(VI) on RSC and SBC as 61.81 % and 76.10 %, respectively. The operation parameters included contact time (15 - 210 minutes), pH of solution (I.O - 10.0), temperature (25, 30, 45 and 55 °C), particle sizes of ads or bents (1.18 mm, 600 f,lm, 300 f,lm and 150 !1m), adsorbents doses (0.04, 0.10, 0.20, 0.40, 0.6 and 1.0 g) and initial concentrations of adsorbates (10, 25, 50, 75 and 100 mg/L). The experimental tests were conducted in batch process. The contact time, amount of adsorbent, temperature, particle size of adsorbent and initial concentration of the metal ions solutions affect the adsorption efficiency but most importantly depended on the pH of solution. The experimental isotherms data were analyzed by using Langmuir and Freundlich equation. The applicability of adsorption was described by using the Freundlich and Langmuir adsorption isotherm. It was found that Langmuir isotherm model fit well the data for nickel(II) and chromium(VI). The measured high linearity of correlation coefficient, R2 and the values dimensionless separation factor, RL indicated a favorable adsorption of both Ni(IJ) and Cr(VI) onto RSC and SBC, respectively. While, the adsorption kinetics, pseudo-first order model, pseudo second order model and intraparticle diffusion model were analyzed on the experimental kinetics data. it was Jouncl that the pseudo second order kinetic model described the adsorption kinetic of both adsorbent well. The performance of both adsorbent in the removal of nickel(l/) and chromium(VI) were also compared It was found that the adsorption capacity of rice straw carbon on nicke/(II) was high may be due to the present of surface oxygen groups, surface charge, high silica content and the properties of nickel. While, the adsorption capacity of sugarcane bagasse carbon on chromium(VI) was high was caused by the high surface area of the adsorbent, surface charge and the properties of chromium.